Medical and nursing students' attitudes to people with mental illness in Nigeria: a tale of two teaching hospitals. Issue 2 (May 2014) - Iheanacho, Theddeus; Stefanovics, Elina; Makanjuola, Victor; Marienfeld, Carla; Rosenheck, Robert
Abstract : This study compared beliefs about and attitudes to mental illness among medical and nursing students at two teaching hospitals in Nigeria with very different levels of psychiatric instructional capacity. Factor analysis of responses to a 43-item self-report questionnaire identified three domains: social acceptance of people with mental illness; belief in non-superstitious causation of mental illness; and stress, trauma and poverty as external causes of mental illness, with entitlement to employment rights. Students at the hospital with a larger, functioning psychiatry department had significantly higher scores on all three factors. Culturally enshrined beliefs and attitudes about mental illness are not uncommon among medical trainees. The availability of psychiatric education and services may have a positive effect on beliefs and attitudes.